Implementation of Class-Based Character Education Strengthening Program in Sidoarjo Regency Elementary Schools: Implementasi Program Penguatan Pendidikan Karakter Berbasis Kelas di Sekolah Dasar Kabupaten Sidoarjo - Azizah, Rida Nur; Kurniawan, Machful Indra (Indonesian Journal of Education Methods Development, 2022)
This research is motivated by the phenomenon of the importance of strengthening classroom-based character education for elementary school students in online learning during the Covid-19 pandemic. During the Covid-19 pandemic, students not only completed learning competencies based on KD (Basic Competencies), but strengthening class-based character education was needed in online learning activities. The application of strengthening class-based character education in the online learning process can be carried out in a persuasive manner. One of the elementary schools that implemented online learning due to the Covid-19 pandemic, namely SDN Sidokumpul, Sidoarjo Regency. In addition, SDN Sidokumpul is an elementary school that implements strengthening class-based character education. The results showed that the implementation of strengthening class-based character education during online learning conditions at SD Negeri Sidokumpul Sidoarjo was carried out by analyzing the characteristics of basic competencies, integrating character values ​​into learning, implementing learning, conducting assessments and evaluating learning. Obstacles when implementing strengthening classroom-based character education during online learning conditions are the teacher cannot apply character values ​​directly in the classroom, the application of character values ​​is carried out persuasively, and teachers cannot assess student character directly, observe and assessing the integration of character values ​​due to online learning conditions. The next solution is to require students to send photos of the implementation of the application of character values ​​at home, require parents to accompany their children to study, and communicate with parents to be able to assess the application of character values. The benefits of this research are expected to provide theoretical input regarding the implementation of a class-based character education strengthening program in online learning during the Covid-19 pandemic in elementary schools, this is regarding the learning process carried out by students at home due to the Covid-19 pandemic. Online learning, Class-Based PPK, Covid-19